Building and Maintaining Trust in a Community-Based Participatory Research Partnership - Christopher, Suzanne; Watts, Vanessa; McCormick, Alma Knows His Gun; Young, Sara (American journal of public health (1971), 2008)
Although intervention research is vital to eliminating health disparities, many groups with health disparities have had negative research experiences, leading to an understandable distrust of researchers and the research process. Community-based participatory research (CBPR) approaches seek to reverse this pattern by building trust between community members and researchers. We highlight strategies for building and maintaining trust from an American Indian CBPR project and focus on 2 levels of trust building and maintaining: (1) between university and community partners and (2) between the initial project team and the larger community. This article was cowritten by community and academic partners; by offering the voices of community partners, it provides a novel and distinctive contribution to the CBPR literature.